Synthesis and Properties of Conjugates between Silver Nanoparticles and DNA-PNA Hybrids - Eidelshtein, Gennady; Halamish, Shay; Lubitz, Irit; Kotlyar, Alexander; Anzola, Marcello; Giannini, Clelia (Journal of Self Assembly and Molecular Electronics, 2023)
We describe the preparation and properties of a stable conjugate between two 15 nm silver nanoparticles (AgNPs) and a DNA-PNA hybrid composed of 10 guanine-cytosine base pairs. We show that the conjugate is spontaneously formed during incubation of a DNA-PNA hybrid, containing phosphoro- thioate residues at both ends of the DNA strand with AgNPs. The conjugate molecules were separated from individual AgNPs and multiparticle structures by gel electrophoresis. We demonstrate that the absorption spectrum of the conjugate is broader than that of AgNPs, due to the interparticle plasmon coupling.